(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The management of the communication of social economy organizations, from cooperatives to non profit organizations, cannot be described as very satisfactory,when the evidence of the visibility, image and perception of citizens is limited, diffuseand not very consistent with reality. Nevertheless, every day more social economy organizations are taking on the relevance of managing their communication with the aim of showing, sensitize and convince the citizenship that another economyand other world are possible.